Introdução à Análise de Movimento usando Visão Computacional - Raquel Ramos Pinho (2004)
With this work we intend to introduce what has been done in the domain of tracking and motion analysis by using computational vision. Therefore in the first chapter of this report we will refer the various types of motion, and analyse the steps that compose a general system of movement capture and analysis, by succinctly describing some works done in this field. Then, in the second chapter we will do a more detailed study about the area of human entire body tracking and motion analysis; namely, in pose recognition and in the recognition of gait and gestures. Finally, in the third and last chapter, emphasis will be given to the medical images analysis and we will summarily exemplify some of its applications.